Answer:
*In Explanation
Step-by-step explanation:
<u>1) Start by just substituting the value of x (given in equation 1) into the second equation:</u>
y = 3x - 1
y = 3(2) - 1
y = 6-1 = 5
<u>2) Since both equations have x on one side, make both equations equal to one another:</u>
2y + 4 = 9 - 3y
<u>Solve for y:</u>
5y = 5
y = 1
<u>Plug y = 1 into either one of the given equations and solve for x:</u>
I'll use first equation:
x = 2y + 4
x = 2(1) + 4
x = 6
<u>3) When substituting X into the second equation, remember to use parenthesis:</u>
The student was substituting x from equation 1 into equation 2, but they forgot to multiply ALL of 2y + 3 by 2.
x = 2y + 3
Substitute into 2nd eqn:
y = 2(2y + 3) - 9
Answer:
Hope this solution helps you
Answer:
25/200
Step-by-step explanation:
Start by multiplying both the top and bottom by 1,000, to get 125/1,000. Then simplify the fraction if you'd like to. For example, you should see that both the top and bottom are dividable by 5, so divide them each by 5 to get 25/200.